Strategic agility in the B2B sharing economy ecosystem of emerging economies : Empirical insights from the Middle East - Abdalla, Samar; Amankwah-Amoah, Joseph; Khan, Zaheer; Hirekhan, Manjusha (Elsevier, 2025)
Strategic agility plays a critical role in enhancing business competitiveness. However, research on how business-to-business (B2B) organizations develop and implement strategic agility within the sharing economy ecosystem remains limited. This study, based on semi-structured interviews with 27 business owners and service/product providers from Egypt who engage in B2B interactions on sharing platforms, identifies two key dimensions of agility that strengthen brand identity and image in emerging markets: (1) the establishment and stabilization of payment frameworks between platforms and providers, and (2) the reinforcement of regulatory measures to ensure a stable working environment. Additionally, the paper examines business activities that facilitate rapid adaptation to external changes, enabling swift responses in B2B exchanges of goods, services, or resources. These findings enhance our understanding of the impact of strategic agility on B2B firms in the sharing economy of emerging markets and offer valuable implications for both research and practice.
Keywords: Strategic Agility; Brand Identity; Emerging Economies; Egypt; Middle East; sharing economy; fi=Kansainvälinen liiketoiminta|en=International Business|